Effects of Soil Burial on Polythene Film Degradation and Associated Bacterial Species - James, Iniobong Ime; Bassey, Hasadiah Okon; Ekong, Esthella Anietie; Akan, Otobong Donald; Ufot, Usenobong Friday; Iwatt, Mfoniso F (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
This study investigated the bacterial degradation of polythene in soil. Polythene bags were obtained from a commercial store, and buried in soil for 45 days (P1) and 90 days (P2). An unburied control (P0) was retained. Soil from the polythene-buried site (S1-S5) and adjacent pristine soil (C1-C5) were obtained for bacteriological analysis. Total heterotrophic bacterial (THB) count of soil samples (C and S) was analyzed using pour plate method on nutrient agar plates. Polythene-degrading bacterial (PDB) counts were obtained after enrichment in mineral salts medium. Polythene degradation was evaluated using Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectrometry. THB ranged from 1.39 ± 0.02 105 CFU/g to 2.79 ± 0.04 105 CFU/g in pristine soil samples. PDB counts were 1.73 ±0.03 102 CFU/g to 2.67 ±.05102 CFU/g. bacterial genera obtained included: Bacillus, Staphylococcus Enterobacter, Micrococcus Pseudomonas Escherichia, Proteus and Alcaligenes species, with occurrences of (%): 18.9, 9.4, 13.4, 4.7, 12.7, 13.5, 21.7 and 5.7 in pristine soil. Escherichia coli, Proteus and Alcaligenes were not observed in plastic debris soil. Variations in the PDB counts and THB counts suggest that a small but significant population of bacteria in the soil can adapt to exposure to polythene burial, becoming capable of polythene degradation. SEM images revealed deterioration of PE surface after burial, with large with cavities, cracks, and holes, consistent with biodegradation process. FT-IR spectra indicated biodegradation, with the disappearance of functional group peaks suggestive microbial metabolism of polythene additives and pro-oxidant, alongside the emergence of a new peaks suggestive of microbial colonization and attack of the oxidative polymeric metrics.